Genetic and Phenotypic Characterization of a Rabies Virus Strain Isolated from a Dog in Tokyo, Japan in the 1940s - Takahashi, Tatsuki; Inukai, Maho; Sasaki, Michihito; Potratz, Madlin; Jarusombuti, Supasiri; Fujii, Yuji; Nishiyama, Shoko; Finke, Stefan; Yamada, Kentaro; Sakai, Hiroki; Sawa, Hirofumi; Nishizono, Akira; et al. (Viruses, 2020)
The rabies virus strain Komatsugawa (Koma), which was isolated from a dog in Tokyo in the 1940s before eradication of rabies in Japan in 1957, is known as the only existent Japanese field strain (street strain). Although this strain potentially provides a useful model to study rabies pathogenesis, little is known about its genetic and phenotypic properties. Notably, this strain underwent serial passages in rodents after isolation, indicating the possibility that it may have lost biological characteristics as a street strain. In this study, to evaluate the utility of the Koma strain for studying rabies pathogenesis, we examined the genetic properties and in vitro and in vivo phenotypes. Genome-wide genetic analyses showed that, consistent with previous findings from partial sequence analyses, the Koma strain is closely related to a Russian street strain within the Arctic-related phylogenetic clade. Phenotypic examinations in vitro revealed that the Koma strain and the representative street strains are less neurotropic than the laboratory strains. Examination by using a mouse model demonstrated that the Koma strain and the street strains are more neuroinvasive than the laboratory strains. These findings indicate that the Koma strain retains phenotypes similar to those of street strains, and is therefore useful for studying rabies pathogenesis.